Microtubule dissassembly in vivo: intercalary destabilization and breakdown of microtubules in the heliozoan Actinocoryne contractilis (The Rockefeller University Press, 1992)
In the marine heliozoan Actinocoryne contractilis, uninterrupted rods of microtubules stiffen the axopodia and the stalk. Stimulation in sea water elicits an extremely fast contraction (millisecond range) accompanied by almost complete Mt dissociation. Using high-speed cinematography and light transmittance measurements, we have studied the process of Mt disassembly in real time. In sea water, Mt disassembly follows an exponential decrease (mean half time of 4 ms) or proceeds by short steps. Cell contraction and Mt disassembly have been inhibited or slowed down through the use of artificial media. Although kinetics are slower (mean half time of 3 s), the curves of the length change against time look similar. The rapid as well as the slower process are accompanied by the formation of breakpoints on the stalk, from which disassembly proceeds. In specimens fixed during the slowed contraction, the presence across the Mt rods, of a single or multiple destabilization band that may consist of granular material and polymorphic forms of tubulin supports the hypothesis of "intercalary destabilization and breakdown" of axonemal Mts.